Types and function of code switching found in the conversation of daniel mananta and raline shah on “daniel tetangga kamu” video youtube channel - Andani, Ni Made Adi; Sulatra, I Komang; Jendra, I Made Indrawan (Journal of Language and Applied Linguistics, 2022)
This study has two purposes, those are (1) to find out the types of code-switching used in conversation between Daniel Mananta and Raline Shah in “Daniel Tetangga Kamu” video YouTube channel and 2) to identify the functions of code-switching used in conversation between Daniel Mananta and Raline Shah’s utterances. A qualitative method is used for this study for analyzing the data collected from five videos. The method is applied to give a clear description of the data according to the theory proposed by Poplack (1980) as cited in Romaine (1989: 122) about the three types of code switching. The result of this analysis showed that there was three types of code switching found in this conversation are; Tag switching, intra-sentential switching and inter-sentential switching. Type of code-switching which is intra-sentential switching is the most often used in conversation between Daniel Mananta and Raline Shah utterances because they was more comfortable when using words, clauses, and phrases in one sentence to convey motivational messages. And the theory proposed by Appel and Muysken (1987) about the six functions of code switching. In this analysis showed that there was six function of code switching are; referential, directive, expressive, phatic, metalinguistic and poetic. Metalinguistic is the dominant function of code-switching in conversation between Daniel Mananta and Raline Shah’s utterances. It occurs because Daniel Mananta and Raline shah wanted to impress the other participants with a show of linguistic skill.